A modified technique of keratoleptynsis ("letter‐box") for treatment of canine corneal edema associated with endothelial dysfunction. (6th September 2020) - Giannikaki, Stamatina; Escanilla, Natalia; Sturgess, Kit; Lowe, Robert C.
Abstract: Purpose: To describe a modified keratoleptynsis procedure, as a method of preserving central corneal function, and evaluate the outcome in vision, reduction of corneal thickness and treatment of epithelial corneal ulcers in cases with endothelial cell dysfunction. Methods: Forty‐four dogs (72 eyes) were affected by progressive corneal edema, with or without ulcerative keratitis. All patients were treated with a dorsal and ventral superficial keratectomy followed by conjunctival flaps, maintaining a clear central cornea. Corneal thickness measurements were obtained via ultrasound biomicroscopy. Results: All eyes showed resolution of ocular discomfort postoperatively, with a median time to resolution of 35 days. Two years post‐surgery, vision had been lost in 2 of 29 eyes (7%). From the initial population, 23 dogs (39 eyes) had follow‐up evaluations of corneal thickness. The mean central corneal thickness was 1359 ± 251 μm prior to surgery. Thickening of the central cornea was observed one week after surgery to 1559 ± 263 μm. Decreased corneal thickness was reported, at 1 month, 4 months, 10 months and 2 years postoperatively (1285 ± 267 μm, 1102 ± 150 μm, 1121 ± 288 μm, 1193 ± 283 μm, respectively). All eyes showed a similar trend of increasing and then decreasing corneal thickness. Conclusions: This surgical technique provided statistically significant reduction in central corneal thickness and sustained relief of ocular pain. Reduction in corneal thickness appeared to be maintained 2 years post‐surgery, and all patients remained comfortable. Superficial corneal pigmentation and fibrosis resulted in vision loss in two eyes.